Respuesta :

Answer:

[tex]f'(x)=\frac{2e^{2x}}{(e^{2x}+1)^2}[/tex]

Step-by-step explanation:

We are given that a function  

[tex]f(x)=\frac{e^{2x}}{e^{2x}+1}[/tex]

We have to find the derivative of the function  

Differentiate w.r.t x

[tex]f'(x)=\frac{2e^{2x}(e^{2x}+1)-2e^{2x}(e^{2x})}{(e^{2x}+1)^2}[/tex]

By using the property

[tex]\frac{d(\frac{u}{v})}{dx}=\frac{u'v-v'u}{v^2}[/tex]

[tex]\frac{d(e^x)}{dx}=e^x[/tex]

[tex]f'(x)=\frac{2e^{4x}+2e^{2x}-2e^{4x}}{(e^{2x}+1)^2}[/tex]

By using property

[tex]a^x\cdot a^y=a^{x+y}[/tex]

[tex]f'(x)=\frac{2e^{2x}}{(e^{2x}+1)^2}[/tex]